Molecular Epidemiology of HIV-1 and HTLV-1/2 Among Female Sex Workers in Four Cities in the State of Para, Northern Brazil - Souza, Ronaldo Lopes de; Pereira, Marcelo Victor Serejo; Silva, Rachel Macedo da; Sales, João Bráullio de Luna; Gardunho, Danilo Cesar Lima; Monteiro, Jacqueline Cortinhas; Siravenha, Leonardo Quintão; Luz, Anderson Luiz Bessa da; Fonseca, Ricardo Roberto de Souza; Oliveira-Filho, Aldemir Branco; Ishak, Marluísa de Oliveira Guimarães; Ishak, Ricardo; et al. (Frontiers in Microbiology, 2020)
Female sex workers (FSWs) represent a key population for the acquisition of sexually transmitted infections (STI) due to their social vulnerability and the risks associated with their occupation. This study was conducted to describe the sociodemographic characteristics and sexual behaviour among FSWs in cities in northern Brazil, to determine the prevalence of human immunodeficiency virus 1 (HIV-1) and human T-cell lymphotropic virus (HTLV-1/2) infections and to identify the circulating subtypes of these agents in this key population. A cross-sectional study using the Time Location Sampling (TLS) method was conducted among 339 FSWs in cities in the state of Pará from 2005 to 2006. Serological and molecular tests were performed to identify infections and viral subtypes, and bivariate and multivariate analyses were conducted to identify risk factors. Most FSWs were young, single, less educated and had at least one child. The prevalence of antibodies against HIV-1 and HTLV-1 was 2.3% and 1.7%, respectively. HIV-1 subtypes B (87.5%) and F1 (12.5%) were identified among FSWs, as were Cosmopolitan subtype (1a) and Transcontinental subgroup (A). Unprotected sex and illicit drug use were associated with HIV-1 and HTLV-1 infections using bivariate and multivariate analyses, and age ≥ 27 years was associated only with HIV. The important information highlighted here clearly indicates that the lack of actions to control and prevent pathogens in FSWs and the lack of strategies for health promotion in key populations can further aggravate the epidemiological scenario of viral infections in remote areas with low human development indices. Neglecting these facts may be causing the spread of these two viruses and their respective subtypes in the general population of northern Brazil.